2021
DOI: 10.1002/adfm.202008783
|View full text |Cite
|
Sign up to set email alerts
|

High‐Performance Aqueous Na–Zn Hybrid Ion Battery Boosted by “Water‐In‐Gel” Electrolyte

Abstract: Aqueous hybrid Na–Zn ion batteries (ASZIBs) are promising for large‐scale energy storage due to their low cost and potential for high output voltage. However, most ASZIBs show limited discharge voltage (<2.0 V) and capacity (<100 mAh g–1) due to inefficient usage of the dual ions. In this study, a novel large‐electrochemical‐window “water‐in‐gel” electrolyte based CuHCF‐CNT/Zn Na–Zn hybrid battery is proposed, which achieves a high extraction voltage of Na ion (2.1 V vs Zn/Zn2+), together with a large discharg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
62
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(64 citation statements)
references
References 59 publications
2
62
0
Order By: Relevance
“…Interestingly, the voltage window can be broadened to 2.1 V benefiting from the synergistic effect of hydrogel and the concentrated salts on suppressing free water activity. [37] The electrochemical reaction kinetic of flexible ZHSC displayed in Figure S13 (Supporting Information) also revealed the dominant position of the surface-driven capacitive process. The specific capacitance was 194.5 F g −1 at 0.5 A g −1 and the capacitance retained 75.4% at 5 A g −1 , indicating excellent rate performance as shown in Figure 6c.…”
Section: Resultsmentioning
confidence: 95%
“…Interestingly, the voltage window can be broadened to 2.1 V benefiting from the synergistic effect of hydrogel and the concentrated salts on suppressing free water activity. [37] The electrochemical reaction kinetic of flexible ZHSC displayed in Figure S13 (Supporting Information) also revealed the dominant position of the surface-driven capacitive process. The specific capacitance was 194.5 F g −1 at 0.5 A g −1 and the capacitance retained 75.4% at 5 A g −1 , indicating excellent rate performance as shown in Figure 6c.…”
Section: Resultsmentioning
confidence: 95%
“…In view of this, it has been proposed to use the polar groups of sodium alginate hydrogels (water‐in‐gel) to capture water molecules and restrict their movement by hydrogen bonding (ESPW >2.7 V, Figure 6 b). [49] Also the carboxylate groups in the gel can provide special channels for ion transport to ensure sufficiently high ionic conductivity. Furthermore, ion‐exchange membrane engineering (decoupled electrolyte, ESPW >3.0 V) can decouple the cathodic and anodic electrolyte to inhibit OER and HER by high concentrations of H + and OH − , respectively (Figure 6 b).…”
Section: Design Strategies For High‐voltage Aqueous Zinc Batteriesmentioning
confidence: 99%
“…113 To avoid the aforementioned problems caused by Zn 2+ insertion/extraction, aqueous Zn hybrid batteries (AZHBs) have been developed using commercial cathode materials for traditional alkali metal ion batteries (LIBs, SIBs, PIBs). 132,133,186 During charge and discharge processes, alkali metal ions (Li + , Na + , K + , Al 3+ , and Mg 2+ ) in the electrolyte participate in the insertion/extraction process in the cathode materials rather than the Zn 2+ . Compared with the traditional aqueous alkali metal ion batteries, AZHBs feature a simplified rechargeable battery configuration, increased operating voltage, extended cycling life, and enhanced energy and power density.…”
Section: Alkali Metal Ions Involved Insertion/ Extractionmentioning
confidence: 99%
“…Importantly, recent progress has demonstrated that cathode materials in Zn‐based batteries exhibited quite different electrochemical behaviors in different electrolytes 113 . To avoid the aforementioned problems caused by Zn 2+ insertion/extraction, aqueous Zn hybrid batteries (AZHBs) have been developed using commercial cathode materials for traditional alkali metal ion batteries (LIBs, SIBs, PIBs) 132,133,186 . During charge and discharge processes, alkali metal ions (Li + , Na + , K + , Al 3+ , and Mg 2+ ) in the electrolyte participate in the insertion/extraction process in the cathode materials rather than the Zn 2+ .…”
Section: Different Reaction Mechanisms Based On the Cathodesmentioning
confidence: 99%